Implementasi Kebijakan Penyelesaian Bank Gagal Tidak Berdampak Sistemik dalam Menjaga Stabilitas Sistem Perbankan di Indonesia (Studi Pada Lembaga Penjamin Simpanan Jakarta) - Rizaldi, Reza Ichsan (Jurnal Administrasi Publik, 2016)
Abstract: Implementation of The Failed Bank Resolution Policy Not Give a System Impact On Securing The Banking System In Indonesia (Studies on Jakarta deposit insurance agency).This study aims to describe and analyze the process of policy implementation does not affect the completion of a failing bank to see if there are systemic factors that influence the policy. This type of research is a kind of research kualitatf descriptive approach to interactive data analysis proposed by Miles. Where in the policy implementation process starts from the determination of banks failed, the process of liquidation and payment of claims. And where in the process of policy implementation, there are two factors that affect communication factors and human resources. As these two factors can affect the implementation of the settlement policy does not affect systemic bank failure in maintaining the stability of the banking system. Conclusions of this study are in the process of policy implementation does not affect the completion of a systemic bank failure, there are four processes such as the establishment of a failed bank and payment of claims. Where there are factors that influence the policy is communication on any existing elements, one of which communication to the public related to 3T as a criterion worth paying for, and the human factor itself is one important factor in the implementation of this policy, in which every employee is required to know all the processes from beginning to end. Keyword: policy implementation, bank failure, and banking system stability Abstrak: Implementasi Kebijakan Penyelesaian Bank Gagal Tidak Berdampak Sistemik dalam Menjaga Stabilitas Sistem Perbankan di Indonesia (Studi Pada Lembaga Penjamin Simpanan Jakarta). Penelitian ini bertujuan untuk mendeskripsikan proses implementasi kebijakan penyelesaian bank gagal tidak berdampak sistemik dengan melihat faktor-faktor yang mempengaruhi kebijakan tersebut. Jenis penelitian ini merupakan penelitian kualitatif deskriptif dengan analisis data interaktif. Hasil dari  penelitian ini yaitu,proses implementasi kebijakan penyelesaian bank gagal tidak berdampak sistemik terdapat empat proses seperti penetapan bank gagal dan pembayaran klaim. Dimana terdapat faktor yang mempengaruhi kebijakan tersebut yaitu komunikasi pada setiap elemen yang ada, salah satunya komunikasi kepada masyarakat terkait 3T sebagai kriteria layak bayar, dan faktor sumber daya manusia sendiri merupakan salah satu faktor penting dalam pelaksanaan kebijakan ini, dimana setiap karyawan dituntut mengetahui semua proses dari awal hingga akhir. Saran dalam penelitian ini adalah pertama, diperlukannya kordinasi rutin LPS dan beberapa lembaga terkait setiap bulannya untuk membahas keadaaan perbankan setiap bulannya dan Kedua,  Selain itu juga adanya pembahasan dimana ada langkah preventif agar tidak terjadi kegagalan bank.   Kata kunci: implementasi kebijakan, bank gagal, dan stabilitas sistem perbankan